Penguatan Peran Rumah Literasi sebagai Upaya Meningkatkan Minat Baca di Desa Sidoharjo, Jambon, Ponorogo - Hanifah Noviandari; Muhamad Tri Hadi Wiyono Tri Hadi (Lentera Salam Institute, 2024)
The reading interest of the community in Sidoharjo Village remains low due to limited access to reading materials and a lack of awareness regarding the importance of literacy. To address this issue, efforts were made to strengthen the role of the Literacy House as a community literacy center. This study aims to formulate strategies for strengthening the Literacy House, identify supporting and inhibiting factors, and analyze the program's impact on increasing community reading interest. The community service methods used include workshops and seminars involving various stakeholders. The results indicate that strategies such as providing relevant book collections, literacy training, and group reading programs effectively enhance community enthusiasm for literacy. Supporting factors include support from the village government and literacy volunteers, while inhibiting factors involve limited funding and low community awareness. Theoretically, this program enriches community literacy studies, while practically, it improves access to reading materials and fosters a culture of literacy. This program is expected to ensure the sustainability of literacy development more optimally